TEKNIK PENGUKURAN TINGKAT KEPARAHAN TRICUSPID REGURGITATION (TR) PADA PASIEN DENGAN PULMONARY HYPERTENSION (PH) - Shahab, Fahmi Idrus; Putri, Dewi Novita; Sandi, Bunga Fadila (UHAMKA Press, 2025)
Background: pulmonary hypertension (PH) is a condition where there is an increase in blood pressure in the pulmonary arteries caused by a blockage of blood vessels to the lungs. Increased pulmonary pressure indicates an increase in right ventricular afterload causing further valve problems, one of which is the occurrence of a leak in the tricuspid valve or often known as Tricuspid Regurgitation (TR). The severity of TR in patients with PH can be measured using echocardiography. Method: case study. Results: an echocardiographic examination was performed on PH patients with the measurement results of the vena contracta 0.6 cm, jet area TR 61 cm. The echocardiography examination procedure uses 3 modalities M-Mode, Color doppler, and Spectrum doppler. Conclusion: the echocardiographic examination procedure in TR patients with PH using 4 measurements obtained moderate and severe results.